Reconstructing real-space geometries of polyatomic molecules undergoing strong field laser-induced Coulomb explosion - Aydin Ashrafi-Belgabad; Reza Karimi; Mohammad Monfared; Kaili Tian; Parviz Parvin; Benji Wales; Éric Bisson; Samuel Beaulieu; Mathieu Giguère; Jean-Claude Kieffer; Philippe Lassonde; François Légaré; et al. (Communications Physics, 2024)
Abstract Coulomb explosion is an established momentum imaging technique, where the molecules are ionized multiple times on a femtosecond time scale before breaking up into ionized fragments. By measuring the momentum of all the ions, information about the initial molecular structure is theoretically available. However, significant geometric changes due to multiple ionizations occur before the explosion, posing a challenge in retrieving the ground-state structure of molecules from the measured momentum values of the fragments. In this work, we investigate theoretically and experimentally such a connection between the ground-state geometry of a polyatomic molecule (OCS) and the detected momenta of ionic fragments from the Coulomb explosion. By relying on time-dependent density functional theory (TDDFT), we can rigorously model the ionization dynamics of the molecule in the tunneling regime. We reproduce the energy release and the Newton plot momentum patterns of an experiment in which OCS is ionized to the 6+ charge state. Our results provide insight into the behavior of molecules during strong field multiple ionization, opening a way toward precision imaging of real-space molecular geometries using tabletop lasers.